Mirrors and Visions: Nu Luu Tho Quan and the Woman Question in Interwar Vietnam - Aitchison, Madeleine (Université d'Ottawa / University of Ottawa, 2023)
This thesis examines the varied output of a small press called Nữ Lưu Thơ Quán (Women’s Bookstore) that operated in Gò Công, Cochinchina from 1928 until 1930. Under the editorial direction of a woman named Phan Thị Bạch Vân (1903-1980), this press sought to influence Vietnamese women’s involvement in their families and communities through novels and biographies, along with instructive and prescriptive literature. Bạch Vân and her cohort of Vietnamese intellectuals derived influence from women’s movements in France, the United States, China, and Japan. They translated a diverse range of ideas and concepts through their own unique lens, with attention paid to their audience and desired influence. I combine literary and historical analyses to consider the significance of works in Nữ Lưu Thơ Quán’s catalogue, such as: Phan Thị Bạch Vân’s novels, Kiếp hoa thảm sử (1928-1929), Nữ anh tài (1928), and Lâm Kiều Loan (1932), the biographies of Madame Roland (1754-1793) and Qiu Jin (1875-1907), and instructive books by Bạch Vân and a writer named Đạm Phương (1881-1947), called Vần Quốc ngữ (1929) and Gia Đình Giáo Dục (1928). This dissertation examines written media that has hitherto been unexplored and shows Vietnamese women’s serious involvement in what contemporaries termed “the Woman’s Question.” Additionally, I show how a director of a small women’s press sought to ensure a remarkable future for the Vietnamese derived from her own vision and through the direction of other women.
Keywords: Vietnam; History; Southeast Asia; Women